Bahasa IndoAnalisis Kesuksesan SIPKD Berdasarkan Model Delone & Mclean Pada Sekretariat Daerah Kabupaten Bulelengnesia - Indra Rai, I Putu G. Lanang; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2019)
The success of an accounting information system in managing regional finances of government agencies is very important to note. Especially if there is a phenomenon of switching from one system to another. The success or failure of the system used can have an impact on employee performance. The purpose of this study is to assess the successful use of the SIPKD based on the DeLone & McLean Model (2003). The study was conducted at the Regional Secretariat of the Regency of Buleleng. This study uses non-probability sampling method with saturated sample technique. The analysis technique used is partial least square analysis. The results of the analysis found that there was a significant influence between the variables of information quality on system use, information quality on user satisfaction, system use on individual performance, and user satisfaction on individual performance. The level of success of the system measured at this level of effectiveness found that the implementation of SIPKD in the Regional Secretariat of Buleleng Regency was classified as successful. Keywords : DeLone & McLean Model; SIPKD; SIA Succes; Individual Performance